Hubungan antara Kepercayaan Diri dengan Self-disclosure Remaja Awal Generasi Z (Jurnal Ilmiah Psikologi MIND SET, 2024)
The Impact of social media on human life, especially early adolescents of Generation Z, is significant as they often share personal information on social media platforms to feel accepted. This study aimed to explore the correlation between self-confidence and self-disclosure among early adolescents who are currently part of Generation Z in Indonesia. This study used a quantitative method with a sample size of 310 participants selected through incidental sampling technique. The research instruments consist of a self-confidence measurement tool (Puspitasari, Retnaningdyastuti & Maulia, 2022) and a self-disclosure measurement instrument (Pohan & Dalimunthe, 2017), which were then modified by the researcher. The analysis revealed a significant positive relationship between self-confidence and self-disclosure. Based on the research findings, which show that most early adolescents of Generation Z have a low level of self-disclosure, it can be a consideration for early adolescents of Generation Z to further improve their self-disclosure to support their social skills.